Maldives : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Maldives. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Maldives' economy grew by 3.9 percent in 2016 and continues to improve in 2017 on a recovery in tourism and a continued strength in construction. The fiscal deficit widened in 2016 driven by lower-than-expected revenue and large arrears clearance despite unchanged current spending. Public debt as a share of GDP rose nearly 11.5 percentage points from 2014-16. The outlook is for a strengthening recovery in the near term, with low inflation, loose financial conditions, but with significant downside risks from a fragile fiscal and external position. Growth is projected to recover in 2017 and stabilize over the medium term.